The inverse problem for the dipole field; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 266, iss. 17 - Epp V. Ya. Vladimir Yakovlevich (2008, 2008)
Title screen